Venous hypertension following average arterious-venous fistula for haemodialysis. - Kojecky, Zdenek; Utikal, Petr; Sekanina, Zdenek; Kocher, Martin; Buriankova, Eva (Biomedical papers, 2002)
The authors emphasize the need for the investigation of the central venous system prior to the insertion of an avfistula, this they consider to be of utmost importance in patients with anamnesis of central vessel access. After the av-fistula is inserted, an unrecognized obstacle (stenosis or thrombosis) may result in the occurrence of venous hypertension and hypofunction, this may lead to av-fistula malfunction.
Keywords: Central venous system / AV-fistula / Venous hypertension